VILLAGE DEVELOPMENT GALLERY (VDG) OF PASIR MUKTI VILLAGE IN BOGOR REGENCY AS A VILLAGE DEVELOPMENT EXHIBITION MEDIA - Lilis Sri Mulyawati; Novida Waskitaningsih; M. Yogie Syahbandar; Lia Amelia Megawati; Ardiatno Yanuadi; M. Azizul Hakim; Asti Dwi Lestari (Research Collaboration Community (RCC), 2023)
Village planning and development currently demands the participation of villagers in developing village potential. Thus, the village government needs to properly socialize the products of spatial planning and village development plans to the villagers, so that they cares more about the development of their area. Unfortunately, many village planning and development products have not been properly socialized. On the other hand, the era of digitalization and the industrial revolution 4.0 demands the information disclosure that can not been met in the most villages. Most of villages currently have less communicative and less informative planning products due to the lack of information media and human resources to compile and present well their spatial planning and development products. Pasir Mukti Village has great economic potential with many metal craft MSMEs spread throughout the village and absorbing a large number of workers. However, the great potential of Pasir Mukti Village has not been fully publicly socialized. Therefore, it is necessary to have a forum or media for information development in Pasir Mukti Village, both in the form of spatial and development planning products, as well as village potential information. In addition, Pasir Mukti Village needs to improve human resource competencies in the preparation process to its dissemination.This community service program aims to empower villagers through several competency improvement trainings, as well as participatory preparation of village development galleries as educational nodes and dissemination of information related to spatial planning, development plans and village potential in Pasir Mukti Village. The objectives of this activity can be achieved through three main stages, including: (1) identification of community needs related to village development galleries and competence in preparing village spatial planning and development, as well as village potential; (2) preparation of village development galleries; and (3) training to increase the competence of the community, who will become managers of the village development gallery.As a result, the program received a very good response from the participants consisting of village officials, Village-Owned Enterprises (BUMDes), Family Welfare Development (PKK), MSME actors, and youth organizations (Karang Taruna). It can be seen from (1) their active participation during FGD and training; (2) their participation and volunteerism to donate a small portion of their MSME products to be displayed in the village development gallery; and (3) their willingness to participate in repairing and enhancing the quality of the gallery building, as well as providing the equipment. Furthermore, the trainees have quite high commitment, that can be seen from their enthusiasm in participating in the FGD and two series of full-time training.Based on the results of these activities, this community service program can (1) increase the knowledge of the Pasir Mukti villagers about the importance of a media/facility as an information center for spatial planning and village development, as well as a medium for promoting village products, education, and public interaction; (2) improve the quality of the human resources of the Pasir Mukti villagers, especially training participants consisting of representatives of village officials, BUMDes, and MSME actors, and (3) build a village development gallery as a new tourist destination in Pasir Mukti Village. Thus, it is hoped that in the long term, this activity can increase the income and welfare of the Pasir Mukti villagers.